OTORITAS HADIS DI MEDIA SOSIAL: ANALISIS VIDEO-VIDEO HADIS DALAM PLATFORM TIKTOK - Jasinal, Rahmat (Jurnal Dakwah Tabligh, 2022)
The advancement of world civilization has touched the ease of spreading Islamic teachings, such as the spread of the Prophet's hadiths through online media. One of the distributions of the Prophet's hadiths is through the TikTok platform. This is a new trend that needs to be explored and discussed. Therefore, this study seeks to examine the authority of hadith on social media, and analysis of hadith videos on the TikTok platform. The question is whether the distribution of hadith in the TikTok media will affect the authority of the hadith and what are the forms of hadith dissemination in the TikTok application. This study uses a qualitative method, where online media is the object of the field. In this study, it is concluded that there are four forms of spreading hadith on the TikTok platform. First, there is the text of the hadith, the translation of the hadith and it is not accompanied by a narrator and there is Salawat music/song as well as an unattractive background. Second, there is no text that only presents a narrator who explains a particular hadith. Third, there are texts and translations as well as interesting backgrounds and added fresh music. Fourth, there is the text of the hadith, the translation of the hadith and there is only the voice of the narrator. And the authority in Tiktok can still be accounted for, among them, comes from account owners who do have knowledge in the field of science.